(untitled) (Research, Society and Development, 2024)
Prostate cancer primarily metastasizes to the bones, resulting in the production of damaged bone matrix and an increase in lymph node chains in the iliac region of the obturator foramen. When identified in advanced stages, this condition presents high morbidity and mortality. The aim of this study is to identify the most prevalent histological grade in cases of advanced prostate cancer with metastasis, to verify if there is concordance between the two values, PSA (Prostate-Specific Antigen) and Gleason Score, in metastatic cancer situations, and to analyze if these two parameters independently influence disease progression. The research is characterized as a retrospective, descriptive study with a quantitative approach. Although a correlation between PSA and the Gleason Score was observed, it was weak, indicating that PSA alone is not a reliable parameter to assess tumor aggressiveness. Additionally, the data revealed that Gleason Score 7 was the most frequent among patients, which may indicate its clinical relevance in the studied population. The implications of this study suggest the need for more effective screening and personalized interventions in the management of prostate cancer. The weak correlation identified between PSA and Gleason emphasizes that healthcare professionals should adopt a multifaceted approach in evaluating patients, taking into account not only these markers but also other clinical factors and biomarkers that may impact the prognosis.